Experiential Marketing Communication of 33RPM Store in Efforts to Retain Vinyl Record Enthusiasts - Rafaelino, Berwyn Muhammad; Mustiawan, Mustiawan; Yuliani, Magvira (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the marketing communication strategy using an experiential marketing approach implemented by 33RPM store in retaining vinyl record enthusiasts amidst the digitalization of the music industry. Employing a descriptive qualitative approach with a case study method, data were collected through in-depth interviews, observation, and documentation involving the store owner, staff, and customers. The results indicate that 33RPM integrates the five elements of experiential marketing: sense, feel, think, act, and relate into its marketing communication strategy. This approach successfully creates a holistic experience that engages the sensory, emotional, cognitive, behavioral, and social aspects of consumers. The store’s unique atmosphere, warm personal interactions, educational approach, interactive experiences, and involvement in the community are key factors in building customer loyalty. These findings affirm that experiential marketing communication is not only effective in attracting consumer attention but also in fostering long-term engagement, helping maintain the existence of physical stores amid the dominance of digital music services. However, this study is limited by the scope of its subject; therefore, future research is recommended to include a broader range of subjects for comparison, in order to produce more objective and comprehensive results.